PSYCHO-EDUCATIONAL ASSISTANCE FOR STUDENTS WITH DISABILITIES FROM INCLUSIVE UNIVERSITY INSTITUTIONS - Racu Serghei; Cebotaru Nina (Sport şi Societate)
In recent years, in the Republic of Moldova, there have been radical changes in the educational system, and one of them specifically aims at the access of young people with disabilities to university studies. This fact has substantially changed the perspective of the authorities, educational specialists, and society in general on disability and, implicitly, on its bearers. The transformation of high schools into inclusive pre-university education institutions brought with it the imperative need to ensure the holders of baccalaureate degrees access to university studies, which meant the launch of their massive transfer to the inclusive education system at the country level. It is a difficult process not only from a financial-economic point of view, although, most of the time, it is specifically referred to by those responsible at all levels, but also from a psychopedagogical, curricular, socio-community, etc. Broadly speaking, among all the problems a university faces, when it assumes the status of an inclusive institution, the material ones are the easiest to solve. Much more difficult is the change at the level of mentality, namely the success or failure of the implementation of inclusive education principles in universities ultimately depends on this aspect.